MEDICINAL PLANT BASED PRODUCTS FOR RURAL COMMUNITY DEVELOPMENT: CASE STUDY OF A MICRO-ENTERPRISE IN MEXICO - IbargÃ¼en, L. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Medicinal plants and herbal products are used extensively throughout Mexico, both in the context of traditional medicine, as well as in popular and domestic medicine (Zolla and Mellado 1995). Unfortunately, commercialization has been characterized as inequitable, poorly regulated and based on unsustainable management practices (Hersch 1999). The aim of the research was to identify and understand those factors which may be crucial to enhance the potential of small scale, rural based initiatives in the area of medicinal plant based products in Mexico. The research is based on a case study of a women’s micro-enterprise, which produces herbal and cosmetic products in a small rural community in the state of Veracruz, Mexico. Ethnographic methods were used and consisted of open ended interviews, participant observation and a community survey. Structured, and semi structured interviews were conducted with key actors in the policy arena. The study concluded that the herbal product market in Mexico presents serious obstacles for small micro-enterprises. Lack of specialized knowledge, limited access to capital investment, and an inhibiting policy framework for these products are some of the main difficulties. The potential impact of medicinal plant product initiatives on income and community development in the present conditions is thus very limited. Zolla, C. and V. Mellado (1995). La funciÃ³n de la medicina domÃ©stica en el medio rural mexicano. Las mujeres y la salud. S. GonzÃ¡lez-Montes. Mexico D.F., El Colegio de MÃ©xico. Hersch-Martinez, P. (1999). ”La flora medicinal silvestre como mercancia.” AntropologÃa Social 35 (Julio/septiembre).